2007
DOI: 10.1002/nbm.1185
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of spinal cord blood volume in humans using vascular‐space‐occupancy MRI

Abstract: Although perfusion is of major interest for many spinal cord disorders, there is no established, reproducible technique for evaluating blood flow or blood volume of the spinal cord in humans. Here the first report of in vivo measurement of human spinal cord blood volume (scBV) is presented. An FDA-approved contrast agent, Gd-DTPA, was used as an intravascular agent for the cord parenchyma, and pre-/post-contrast vascular-space-occupancy (VASO) MRI experiments were performed to obtain a quantitative estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Furthermore, in accordance with Hoy et al who found a plasma volume of 1 ml/100 g, which corresponds to V of 1.56 ml/100 g in dogs using radioactively labeled plasma proteins [22], we obtained a similar median value of V (about 1 ml/100 g using either an AIF in the VA or in the ICA). Finally, a recent study [1] of the spinal cord blood volume in humans using perfusionweighted MRI reported higher values (approximately 4.3 ml/100 g), which may be attributed to the different modalities, as the results between CT and MRI may not be directly interchangeable [23], as well as to the known overestimation of the blood volume by using T1-weighted steady-state methods [24].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, in accordance with Hoy et al who found a plasma volume of 1 ml/100 g, which corresponds to V of 1.56 ml/100 g in dogs using radioactively labeled plasma proteins [22], we obtained a similar median value of V (about 1 ml/100 g using either an AIF in the VA or in the ICA). Finally, a recent study [1] of the spinal cord blood volume in humans using perfusionweighted MRI reported higher values (approximately 4.3 ml/100 g), which may be attributed to the different modalities, as the results between CT and MRI may not be directly interchangeable [23], as well as to the known overestimation of the blood volume by using T1-weighted steady-state methods [24].…”
Section: Discussionmentioning
confidence: 90%
“…The dynamic contrast-enhanced CT or MRI has been increasingly utilised in the last years for quantifying hemodynamics in the brain and in other organs (such as the head and neck, lung, liver, intestine, kidney, prostate and muscle), but there is scarce evidence for perfusionweighted MR imaging of the spinal cord in humans [1,2], and there are no initial data using perfusion CT imaging. Today, two commercially available software packages are widely used for quantification of perfusion CT studies.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the missing spinal arterial flow is difficult to estimate because there are no reliable reports of this quantity. 32 However, this missing flow is likely a small fraction compared with the blood flow to the brain, and thus the resulting underestimation of PVI CC is also small.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive MR perfusion and vascular permeability techniques being developed in step with spinal DT imaging protocols may provide more definitive evidence. 18,26 Regardless of the mechanism, reproducible patterns of neural degeneration are found on imaging modalities such as DT studies.…”
Section: Pathophysiological Features Of Csm In Opllmentioning
confidence: 99%